Chronic wounds in persons living with dementia: An integrative review. (18th January 2022) - Sefcik, Justine S.; McLaurin, Elease J.; Bass, Ellen J.; DiMaria‐Ghalili, Rose Ann
Abstract: Background: Persons living with dementia (PLWD) are at risk for chronic wounds; however, they are rarely included in research. Objectives: To inform practice and research directions, the aim of this integrative review was to identify and synthesise previous knowledge about the characteristics of chronic wounds in PLWD, in terms of chronic wound types, prevalence, setting and interventions. Design: A literature search was conducted for publications in English using PubMed, Web of Science and CINAHL. The minimum information required for inclusion was how many PLWD enrolled in the study had wounds. Methods: This integrative review followed the Whittemore and Knafl methodology. Data extraction and synthesis were guided by a directed content analysis, with a coding structure based on an initial review of the literature. Results: Thirty‐six articles met the inclusion criteria. The majority were missing characteristics of PLWD including severity of dementia and race/ethnicity/nationality, and none mentioned skin tone. Most focused on pressure injuries in the nursing home and acute care setting. Few included information on interventions. Only one discussed challenges of wound care for a PLWD exhibiting aggression. Conclusion: There is a gap in the literature regarding PLWD and chronic wounds other than pressure injuries that are common in older adults (e.g. diabetic foot ulcers, venous leg ulcers). Research is warranted among those PLWD who live alone and those who receive wound care from family caregivers to understand experiences. Knowledge can inform the development of future novel interventions for wound healing. Future research is needed regarding chronic wounds in those who exhibit behavioural and psychological symptoms of dementia. Relevance to Clinical Practice: Nurses that care for chronic wounds in PLWD can contribute their knowledge to include information in guidelines on best care practices and contribute their perspective to research teams for future research.